2008
DOI: 10.1002/ijc.23450
|View full text |Cite
|
Sign up to set email alerts
|

SPARC‐induced increase in glioma matrix and decrease in vascularity are associated with reduced VEGF expression and secretion

Abstract: Glioblastomas are heterogeneous tumors displaying regions of necrosis, proliferation, angiogenesis, apoptosis and invasion. SPARC, a matricellular protein that negatively regulates angiogenesis and cell proliferation, but enhances cell deadhesion from matrix, is upregulated in gliomas (Grades II–IV). We previously demonstrated that SPARC promotes invasion while concomitantly decreasing tumor growth, in part by decreasing proliferation of the tumor cells. In other cancer types, SPARC has been shown to influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…Recent reports showed that SPARC inhibits microvascular endothelial cell proliferation by blocking VEGF-A. 30,31,33,34 To examine the relationship between SPARC and VEGF-A, we assessed cytoplasmic expression of VEGF-A in cancer cells versus SPARC in CRC and stromal cells using IHC staining intensity. An inverse correlation between VEGF-A and stromal cell SPARC staining intensity, but not between VEGF-A and CRC cell SPARC, was demonstrated (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports showed that SPARC inhibits microvascular endothelial cell proliferation by blocking VEGF-A. 30,31,33,34 To examine the relationship between SPARC and VEGF-A, we assessed cytoplasmic expression of VEGF-A in cancer cells versus SPARC in CRC and stromal cells using IHC staining intensity. An inverse correlation between VEGF-A and stromal cell SPARC staining intensity, but not between VEGF-A and CRC cell SPARC, was demonstrated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SPARC has been associated with reduced vascularity and hypoxia, 9 which are events linked to VEGF-A suppression in tumors. 30,31 HSP27, one of the smallest HSPs, has been associated with clinical outcomes in different solid tumors, including a positive correlation with SPARC in gliomas. 32 In our study, IHC analysis demonstrated that HSP27 expression in CRC was proportionately correlated with expression of SPARC in stromal cells but not in SPARC cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The SPARC modulates glioma growth by altering the tumour microenvironment and suppressing tumour vascularity through suppression of VEGF expression and secretion. (Yunker et al, 2008). In this context, the suppression of angiogenesis-mediated tumour growth by SPARC in medulloblastoma seems to be the consequence of its ability to inhibit the expression of angiogenic factors such as MMP-9, bFGF and VEGF in tumour tissues, which may in turn inhibit capillary infiltration into tumours.…”
Section: Discussionmentioning
confidence: 99%
“…106 Expression of SPARC in the nervous system is limited to the angiogenic microvasculature, as well as the locus coeruleus and retinal astrocytes, but is not normally expressed in the cerebral cortex. [107][108][109][110] However, SPARC expression is present in both tumor cells and endothelial cells in gliomas of all grades, as well as in endothelial cells and astrocytes in the adjacent tissue. 111 Recent work indicates that SPARC suppresses tumor vascularity via suppression of VEGF expression and secretion, which is accomplished by limiting the availability of the growth factor.…”
Section: Anti-angiogenic Factorsmentioning
confidence: 99%
“…111 Recent work indicates that SPARC suppresses tumor vascularity via suppression of VEGF expression and secretion, which is accomplished by limiting the availability of the growth factor. 110 In contrast to its negative effect on angiogenesis, SPARC appears to have a promoting effect on tumor invasiveness. 112,113 A better understanding of these pathways is necessary before proceeding with anti-SPARC therapies.…”
Section: Anti-angiogenic Factorsmentioning
confidence: 99%